First study of pathogen load and localisation of ovine footrot using fluorescence in situ hybridisation (FISH) - Witcomb, Luci A. (Vet Microbiol, 2015)
Analysis of bacterial populations in situ provides insights into pathogen population dynamics and potential reservoirs for disease. Here we report a culture-independent study of ovine footrot (FR); a debilitating bacterial disease that has significant economic impact on sheep farming worldwide. Disease begins as an interdigital dermatitis (ID), which may then progress to separation of the hoof horn from the underlying epidermis causing severe footrot (SFR). Dichelobacter nodosus is the causative agent of ovine FR, however, the role of Fusobacterium necrophorum and other bacteria present in the environment and on the feet of sheep is less clear. The objective of this study was to use fluorescence in situ hybridisation (FISH) to detect, localise and quantify D. nodosus, F. necrophorum and the domain Bacteria from interdigital skin biopsies of healthy, ID- and SFR-affected feet. D. nodosus and F. necrophorum populations were restricted primarily to the epidermis, but both were detected more frequently in feet with ID or SFR than in healthy feet. D. nodosus cell counts were significantly higher in feet with ID and SFR (p < 0.05) than healthy feet, whereas F. necrophorum cell counts were significantly higher only in feet with SFR (p < 0.05) than healthy feet. These results, together with other published data, indicate that D. nodosus likely drives pathogenesis of footrot from initiation of ID to SFR; with D. nodosus cell counts increasing prior to onset of ID and SFR. In contrast, F. necrophorum cell counts increase after SFR onset, which may suggest an accessory role in disease pathogenesis, possibly contributing to the severity and duration of SFR.